Use of volatile fingerprints for rapid screening of antifungal agents for efficacy against dermatophyte Trichophyton species - Naraghi, Kamran; Sahgal, Natasha; Adriaans, Beverley; Barr, Hugh; Magan, Naresh (Elsevier, 2010)
The potential of using an electronic nose (E-nose) as a rapid technique for screening the responses of dermatophytes to antifungal agents was studied. In vitro, the 50% and 90% effective concentration (EC) values of five antifungal agents including fungicides and antioxidant mixtures against Trichophyton rubrum and Trichophyton mentagrophytes were obtained by mycelial growth assays. The qualitative volatile production patterns of the growth responses of these fungi to the EC values incorporated into solid media were analysed after 96-120h incubation at 25°C using headspace analyses using five replicates per treatment. Overall, results, using principal components analysis and cluster analysis, demonstrated that it was possible to differentiate between various treatments within 96-120h of growth. The EC50 values were discriminated from the controls while the EC90 concentration treatments were often grouped with the agar blanks because of very slow growth. This study showed that potential exists for using qualitative volatile patterns as a rapid screening method for antifungal agents against micro-organisms. This approach could significantly improve and facilitate the monitoring of antimicrobial drug activities and infection control programmes and perhaps also for monitoring of drug resistance buildup in microbial populations